2020
DOI: 10.3928/01913913-20200120-01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of All Causes of Visual Function Loss in Children With Congenital Blepharoptosis

Abstract: Purpose: To evaluate the overall frequency of visual function loss in pediatric patients with congenital blepharoptosis. Methods: This retrospective study was conducted in a tertiary center. The clinical records of patients younger than 18 years who were diagnosed as having congenital blephroptosis, underwent surgery, and had at least 1 year of postoperative follow-up were evaluated. Visual acuity results, presence of structural eye abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…In the present study, the incidence of amblyopia in patients with congenital ptosis was 23%, similar to previous reports [ 21 23 ]. In addition, all amblyopic eyes in this study were ptotic, revealing that in patients with unilateral congenital ptosis, amblyopia was found more often in ptotic eyes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the incidence of amblyopia in patients with congenital ptosis was 23%, similar to previous reports [ 21 23 ]. In addition, all amblyopic eyes in this study were ptotic, revealing that in patients with unilateral congenital ptosis, amblyopia was found more often in ptotic eyes.…”
Section: Discussionsupporting
confidence: 93%
“…It has been established that congenital ptosis may increase the incidence of refractive errors, including myopia, hyperopia, and astigmatism, as well as the incidence of amblyopia and anisometropia [ 1 , 19 , 20 ]. In addition, due to amblyopia or deprivation caused by a drooping eyelid covering the pupil, congenital ptosis may have a negative influence on visual acuity [ 21 ]. Our study revealed that patients with congenital ptosis are more likely to experience visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the incidence of amblyopia in patients with congenital ptosis is 20%, similar to previous reports. [21,22,23] Besides, all cases of amblyopia in this study were ptotic eyes, revealing that in cases with unilateral congenital ptosis, amblyopia was found more often in ptotic eyes. When it comes to the causes of amblyopia in patients with congenital ptosis, astigmatism made up to the largest proportion.…”
Section: Discussionsupporting
confidence: 51%
“…[1,19,20] Besides, due to amblyopia or deprivation caused by drooping eyelid covering the pupil, congenital ptosis may have a bad in uence on visual acuity. [21] Our study revealed that patients with congenital ptosis are more likely to suffer from visual impairment. Among the 25 patients with unilateral ptosis, the BCVA in ptotic eyes is lower than that in fellow normal eyes, which indicated that congenital ptosis may lead to visual defects.…”
Section: Discussionmentioning
confidence: 61%